Editorial: The Problems and Prospects of Trafficking Prosecutions: Ending impunity and securing justice - Gallagher, Anne T (Anti-Trafficking Review, 2016)
Having been guest editor of the very first issue of the Anti-Trafficking Review, it was with great pleasure that I accepted the invitation of the editorial board to oversee the production of its sixth issue. Back in 2012 I identified the emergence of the Anti-Trafficking Review, thefirst specialist journal on human trafficking, as a watershed moment, signalling the transformation of‘trafficking’ from a niche (perhaps even a fringe) academic sub-discipline into a legitimate, substantial and discrete area of study. The past four years since its launch have vindicated that assessment. New specialist journals on trafficking and its variants have been launched, and the range and depth of research being undertaken in this field has significantly expanded. While law, sociology and human rights continue to be the dominant lenses through which trafficking is studied, analysed and explained, there is no denying the expanding and enriching influence of other disciplines: from geography to anthropology; from health sciences to migration studies. These changes in research and writing around trafficking have brought tangible benefits: helping improve our understanding of what is happening and why, as well as strengthening the evidence base on which credible, effective responses can be built.